Integration Methods Used in Numerical Simulations of Electromagnetic Transients - Silva, R. C. [UNESP]; Kurokawa, S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper made an analysis of some numerical integration methods that can be used in electromagnetic transient simulations. Among the existing methods, we analyzed the trapezoidal integration method (or Heun formula), Simpson's Rule and Runge-Kutta. These methods were used in simulations of electromagnetic transients in power systems, resulting from switching operations and maneuvers that occur in transmission lines. Analyzed the characteristics such as accuracy, computation time and robustness of the methods of integration.
Keywords: Electromagnetic transients; transmission lines; electric power; numerical methods; cascade of pi-circuits